Lung aeration, ventilation, and perfusion imaging. Issue 3 (June 2022) - Ball, Lorenzo; Scaramuzzo, Gaetano; Herrmann, Jacob; Cereda, Maurizio
Abstract : Purpose of review: Lung imaging is a cornerstone of the management of patients admitted to the intensive care unit (ICU), providing anatomical and functional information on the respiratory system function. The aim of this review is to provide an overview of mechanisms and applications of conventional and emerging lung imaging techniques in critically ill patients. Recent findings: Chest radiographs provide information on lung structure and have several limitations in the ICU setting; however, scoring systems can be used to stratify patient severity and predict clinical outcomes. Computed tomography (CT) is the gold standard for assessment of lung aeration but requires moving the patients to the CT facility. Dual-energy CT has been recently applied to simultaneous study of lung aeration and perfusion in patients with respiratory failure. Lung ultrasound has an established role in the routine bedside assessment of ICU patients, but has poor spatial resolution and largely relies on the analysis of artifacts. Electrical impedance tomography is an emerging technique capable of depicting ventilation and perfusion at the bedside and at the regional level. Summary: Clinicians should be confident with the technical aspects, indications, and limitations of each lung imaging technique to improve patient care.